Mummies in the morning - Osborne, Mary Pope. (New York : Random House, 1993)
Jack and his younger sister take a trip in their tree house back to ancient Egypt, where they help a queen's mummy continue her voyage to the Next Life.
"A First stepping stone book."
"RL:2.0"--P. [4] of cover.
"006-009"--P. [4] of cover.
Keywords: Time travel -- Fiction; Mummies -- Fiction; Magic -- Fiction; Tree houses -- Fiction